Regeneration of Spinal Cord Connectivity Through Stem Cell Transplantation and Biomaterial Scaffolds - Katoh, Hiroyuki; Yokota, Kazuya; Fehlings, Michael G. (Frontiers in Cellular Neuroscience, 2019)
Significant progress has been made in the treatment of spinal cord injury (SCI). Advances in post-trauma management and intensive rehabilitation have significantly improved the prognosis of SCI and converted what was once an “ailment not to be treated” into a survivable injury, but the cold hard fact is that we still do not have a validated method to improve the paralysis of SCI. The irreversible functional impairment of the injured spinal cord is caused by the disruption of neuronal transduction across the injury lesion, which is brought about by demyelination, axonal degeneration, and loss of synapses. Furthermore, refractory substrates generated in the injured spinal cord inhibit spontaneous recovery. The discovery of the regenerative capability of central nervous system neurons in the proper environment and the verification of neural stem cells in the spinal cord once incited hope that a cure for SCI was on the horizon. That hope was gradually replaced with mounting frustration when neuroprotective drugs, cell transplantation, and strategies to enhance remyelination, axonal regeneration, and neuronal plasticity demonstrated significant improvement in animal models of SCI but did not translate into a cure in human patients. However, recent advances in SCI research have greatly increased our understanding of the fundamental processes underlying SCI and fostered increasing optimism that these multiple treatment strategies are finally coming together to bring about a new era in which we will be able to propose encouraging therapies that will lead to appreciable improvements in SCI patients. In this review, we outline the pathophysiology of SCI that makes the spinal cord refractory to regeneration and discuss the research that has been done with cell replacement and biomaterial implantation strategies, both by itself and as a combined treatment. We will focus on the capacity of these strategies to facilitate the regeneration of neural connectivity necessary to achieve meaningful functional recovery after SCI.